Liposomes with cyclodextrin channels and polyethyleneimine (PEI) improves cytoplasmic vaccine delivery and induces anti-cancer immune activity in mice. (2nd January 2022) - Lee, Arnold; Dadhwal, Sumit; Gamble, Allan; Hook, Sarah
Abstract: Cancer vaccines have been developed as an additional method of treatment in the fight against cancer. However, an important barrier to an effective vaccine is the inefficient presentation of exogenous antigen by dendritic cells to cytotoxic CD8 T cells. In this study, DPPC liposomes were modified with channels and loaded with polyethyleneimine (PEI) and 5, 6-dimethylxanthenone-4-acetic acid (DMXAA) to produce a vaccine carrier. The liposomes were designed to be pH responsive to facilitate delivery of antigens directly to the cytoplasm of antigen presenting cells, bypassing the cross-presentation pathway and improving cellular immune responses. The lysis of liposomes in acidic cell-free conditions was measured using a validated dynamic light scattering assay in order to gain an insight into the mechanism of PEI-mediated lysis. Dendritic cell stimulation and T cell proliferation was investigated in vitro and the potential of this formulation to stimulate a therapeutic anti-cancer immune response was examined in a murine melanoma model. The modified formulation stimulated T cell activation in vitro and induced a small but significant increase in survival in immunized mice. Overall, liposomes modified with PEI and channels successfully delivered antigen to the cytoplasm of dendritic cells, which subsequently led to the development of an appropriate immune response.